PRINSIP HARMONISASI DALAM PENGELOLAAN SUMBER DAYA LAUT DI DAERAH KEPULAUAN INDONESIA - M Ridwan (TAHKIM, 2017)
Indonesia's resources are essentially sourced from the maritime sector that can be well developed so as to help the region to achieve economic, social and political objectives. The development of the maritime sector can also contribute to the integrity of the economy, through increased production, industry, services and self-sufficiency in the maritime sector. The management of marine resources based on the diversity of people, can provide justice for the community, because the community is involved both in the process of planning, implementation, implementation and evaluation and monitoring, so that the rights of the community can be fulfilled both jurisdic and economically.